Validity and Responsiveness of the Glittre-ADL Test without a Backpack in People with Chronic Obstructive Pulmonary Disease. (3rd July 2020) - Mendes, Liliane P. de Souza; Parreira, Verônica Franco; Spencer, Lissa M.; Vieira, Danielle Soares Rocha; Alison, Jennifer Ailsey
Abstract: The Glittre-ADL test assesses the functional capacity for activities of daily living of people with chronic obstructive pulmonary disease (COPD). In the test, a weighted backpack is worn (2.5 kg for women and 5.0 kg for men). The differential in weight between men and women is not common in other tests of exercise capacity and may limit the comparison of the test between sexes. The primary aim of this study was to validate the Glittre-ADL test performed without the backpack in people with COPD. Forty participants with mild to severe COPD (mean ± SD age: 70 ± 6 years; FEV1 : 48 ± 20%predicted) were recruited and performed two six-minute walk tests (visit 1); two Glittre-ADL tests with backpack (visit 2), and the Glittre-ADL test with and without the backpack, in random order (visit 3). The Glittre-ADL test time was shorter without the backpack than with the backpack [mean difference −0.37 min (95%CI −0.59 to −0.15)] and heart rate (HR) and oxygen saturation (SpO2 ) were equivalents between tests [−1.31 beats/minute (−3.92 to 1.30) and −0.95% (−2.27 to 0.37), respectively]. The Glittre-ADL test without the backpack elicited similar HR and SpO2 responses as the test with the backpack, indicating equivalence of physiological demand. Thus, the Glittre-ADL test without the backpack was a valid, responsive, and appropriate test to assess functional capacity for activities of daily living.